2020
DOI: 10.1039/d0tc02346a
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and reliability enhancement of atomic layer deposited thin films by in situ atomic layer substrate biasing

Abstract: A novel “atomic layer substrate biasing (ALSB)” technique is proposed to improve the dielectric properties including the film density, the dielectric constant (K), the leakage current density (Jg), and the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…One can see that the TiN capping layer effect contributes to a significant increase in the ZrO 2 film density (4.99 g/cm 3 for Z0 vs 5.39 g/cm 3 for Z0T and 5.23 g/cm 3 for ZA vs 5.51 g/cm 3 for ZAT), which is ascribed to an increase of the ZrO 2 crystallinity due to the stress induced by the TiN capping layer. The film density of the ZrO 2 layers is also increased by the ALA treatment (4.99 g/cm 3 for Z0 vs 5.23 g/cm 3 for ZA and 5.39 g/cm 3 for Z0T vs 5.51 g/cm 3 for ZAT), indicating that the adatom migration enhanced by the in situ ALA treatment results in the film densification of ZrO 2 . The incidence of plasma species during the ALA treatment also generates compressive stress in the out-of-plane direction, resulting in an increase in the film density. , An increase in the film density is usually accompanied by a reduction in the defect density. A decrease in the amount of oxygen vacancies by the ALA treatment has been confirmed by the O 1s X-ray photoelectron spectroscopy of the ZrO 2 layers, which has been revealed in our previous work. , Upon the TiN capping layer effect and the ALA treatment, the ZrO 2 film density was effectively increased to approach that of the bulk ZrO 2 (5.68 g/cm 3 ) …”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…One can see that the TiN capping layer effect contributes to a significant increase in the ZrO 2 film density (4.99 g/cm 3 for Z0 vs 5.39 g/cm 3 for Z0T and 5.23 g/cm 3 for ZA vs 5.51 g/cm 3 for ZAT), which is ascribed to an increase of the ZrO 2 crystallinity due to the stress induced by the TiN capping layer. The film density of the ZrO 2 layers is also increased by the ALA treatment (4.99 g/cm 3 for Z0 vs 5.23 g/cm 3 for ZA and 5.39 g/cm 3 for Z0T vs 5.51 g/cm 3 for ZAT), indicating that the adatom migration enhanced by the in situ ALA treatment results in the film densification of ZrO 2 . The incidence of plasma species during the ALA treatment also generates compressive stress in the out-of-plane direction, resulting in an increase in the film density. , An increase in the film density is usually accompanied by a reduction in the defect density. A decrease in the amount of oxygen vacancies by the ALA treatment has been confirmed by the O 1s X-ray photoelectron spectroscopy of the ZrO 2 layers, which has been revealed in our previous work. , Upon the TiN capping layer effect and the ALA treatment, the ZrO 2 film density was effectively increased to approach that of the bulk ZrO 2 (5.68 g/cm 3 ) …”
Section: Resultsmentioning
confidence: 73%
“…On the other hand, the leakage current densities at +1 V, as shown in Figure (b) and (c), were significantly suppressed by ∼60% (1.05 × 10 –7 A/cm 2 for Z0 vs 4.27 × 10 –8 A/cm 2 for ZA) and ∼90% (2.39 × 10 –7 A/cm 2 for Z0T vs 2.40 × 10 –8 A/cm 2 for ZAT) by the ALA treatment, which can be deduced from the film densification as revealed in the XRR measurement (Figure ). It has been reported that an increase in the film density is correlated with a decrease in the defect (such as oxygen vacancies) density and coalescence of grain boundaries, ,, which thereby reduces the trap density and leakage current paths. The result demonstrates that the in situ ALA treatment can significantly suppress the leakage current through the nanoscale ZrO 2 layer in MIM capacitors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the substrate biasing technique has shown immense potential in PEALD thin-film development, where ion energies can be tuned by varying the bias voltage at the substrate stage to modify the material properties mentioned above. , Surface reactions involving enhanced reactivity and adatom diffusion are favored for ions of medium energies in the range of 30–150 eV. Ions with energies larger than 150 eV may lead to subsurface implantation, sputtering, or roughening of the PEALD thin films. , Optimum deposition conditions must be carefully evaluated to obtain thin films with appropriate properties for complex optical coatings, such as mirrors, narrow bandpass filters, beamsplitters, etc.…”
Section: Introductionmentioning
confidence: 99%